Analyzing Society's Approach to Rape Victims - Agrawal, Aryan (Happiness: Journal of Psychology and Islamic Science, 2025)
This study investigates the complex and often regressive social responses to rape victims, highlighting the persistent stigmatization, victim-blaming, and institutional neglect they experience. Even in the face of changing legal contexts and heightened public sensitivity, victims are often confronted with hostility, suspicion, and exclusion that erode justice and emotional healing. By integrating different socio-legal approaches from linguistic research into rape sentencing and sociocultural assessments across South Asian realities, this article highlights how patriarchal ideology, religious meaning-making, and honor ideologies create a culture of impunity and silence. Institutional limitations in the form of underreporting, police indifference, procedural failures, and a culture of shame that both disempower and disempower victims from reporting crimes are discussed. The discussion also covers legal solutions, state obligations, and new activism to redefine the discourse of sexual violence. Finally, the paper seeks a multifaceted critique of current societal responses, calling for survivor-centered reforms, educational campaigns, and institutional accountability to change attitudes in society and in courts. Through this in-depth analysis, this research hopes to create a more empathetic, more informed, and more just environment for rape survivors.